Potensi dan Strategi Ekowisata Kreatif Berbasis Mangrove di Desa Jerowaru Kabupaten Lombok Timur - Anggriani, Anggi; Damayanti, Ayu Adhita; Larasati, Chandrika Eka (Jurnal Ilmu Kelautan Lesser Sunda, 2024)
Jerowaru Village is one of the tourist villages in Jerowaru District, East Lombok Regency. Jerowaru Village has the potential for natural beauty in the form of beaches and tens of hectares of mangrove trees which are still natural and have been preserved. The method used is primary and secondary data, where primary data includes association biota, community participation & perception and stakeholder participation and secondary data includes mangrove density. Sample collection was carried out at five sampling points around the mangrove which represented the habitat of the associated biota using 1x1m quadrants. The results show that there are 11 types of association biota, including Cassidula aurisfeli, Cassidula nucleus, Cassidula sp, Littoraria scabra, Monodonta consufa, Nerita lineata, Nerita undata, Pila scutata, Pythia scarabeus, Strobus mutabilis, Terebralia sulcata. Also, there is 1 type of Bivalvia, namely Perna viridis. Developing all existing potential such as vegetation potential or mangrove density, associated biota, supporting facilities for mangrove tourism forests, as an alternative environment-based tourism to meet the demand of the people of East Lombok for tourism needs. Based on the average density value at each station, station I has a density value of 0.15 ind/m2. Station II has a density of 0.09 ind/m2 and station III has a density value of 0.06 ind/m2.